Plasmon chemistry on ag nanostars: experimental and theoretical raman/sers study of the pesticide thiacloprid bond cleavage by the plasmon deactivation effect - Celis, Freddy; Aracena Astudillo, Andrés Osvaldo.; García, Macarena; Segura del Río, Rodrigo.; Sánchez Cortes, Santiago.; Leyton, Patricio (American Chemical Society, 2023)
Silver nanoparticles (AgNPs) were synthetized and employed in surface-enhanced Raman scattering measurements to study the chemical behavior when thiacloprid (Thia) interacts with the surface of Ag nanospheres (AgNSp) and Ag nanostars (AgNSt) upon excitation of the system with a 785 nm laser. Experimental results show that the deactivation of the localized surface plasmon resonance induces structural changes in Thia. When AgNSp are used, it is possible to observe a mesomeric effect in the cyanamide moiety. On the other hand, when AgNSt are employed, it promotes the cleavage of the methylene (−CH2−) bridge in Thia to produce two molecular fragments. To support these results, theoretical calculations based on topological parameters described by the atoms in molecules theory, Laplacian of the electron density at the bond critical point (∇2ρ BCP), Laplacian bond order, and bond dissociation energies were made, confirming that the bond cleavage is centered at the −CH2- bridge in Thia.
Keywords: Scattering sers; Degradation; Transferencia de carga; Nanoestructuras